Pemahaman Hadis Israf Dan Korelasinya Dengan Fanatisme Netizen - Pian, Okta; Hedhri Nadhiran (Ta’wiluna: Jurnal Ilmu Al-Qur'an, Tafsir dan Pemikiran Islam, 2025)
Israf can be interpreted as a behavior or attitude that exceeds limits or is excessive in every action. This phenomenon of behavior often occurs among netizens who are targeted with excessive praise towards certain figures or anger that exceeds limits when those figures are criticized by others. For example, the writer found an account on TikTok @Lautan.ungu that contains K-pop fans and soccer fans who share the same idol but constantly insult and attack each other. This phenomenon frequently occurs even though it is done without face-to-face interaction, making it interesting to study. As for the hadith perspective, it was chosen as an approach because hadith serves as an explanation of the Quran. To address the issues in this research, the researcher used the Ma'anil Hadis method according to the steps set by the muhaddis. The results of this research show that the israf behavior of netizens in the hadith perspective is not allowed, but when praise or admiration is still within limits to provide motivation, it is not problem.